Training Methods to Improve Sports Performance and Health - Gonçalves, Bruno (2022)
There are several types of training methods aiming to develop sport performance and improve health indicators. Fundamentally, training methods are the result of manipulating different training variables, and the possibility of combining these variables is vast. Therefore, the search to study the effect of these constraints on sports and health, considering specific contexts and taking into account the magnitude of inter-individual responses, will afford a better understanding of the training interventions. At the same time, over the years, numerous innovations and technological advances have been introduced to assist the development of athletes’ performance and monitor individual lifestyles. These advances have changed how the training may be conducted, controlled, and evaluated. For example, in sport settings, using technology to collect intense and continuous data of athletes’ activity in their natural environments appears as an innovative and promising step. In health, the enormous diversity of training methods supporting healthy lifestyles and innovative approaches is arising, especially but not only from improved information gathered through technological development.